In Vitro Generation of Atrioventricular Heart Valve Neoscaffolds. Issue 7 (20th May 2014) - Weymann, Alexander; Radovits, Tamás; Schmack, Bastian; Li, Shiliang; Korkmaz, Sevil; Soós, Pál; Istók, Roland; Veres, Gabor; Chaimow, Nicole; Karck, Matthias; Szabó, Gábor
Abstract Tissue engineering of cardiovascular structures represents a novel approach to improve clinical strategies in heart valve disease treatment. The aim of this study was to engineer decellularized atrioventricular heart valve neoscaffolds with an intact ultrastructure and to reseed them with umbilical cord‐derived endothelial cells under physiological conditions in a bioreactor environment. Mitral (n = 38) and tricuspid (n = 36) valves were harvested from 40 hearts of German Landrace swine from a selected abattoir. Decellularization of atrioventricular heart valves was achieved by a detergent‐based cell extraction protocol. Evaluation of the decellularization method was conducted with light microscopy and quantitative analysis of collagen and elastin content. The presence of residual DNA within the decellularized atrioventricular heart valves was determined with spectrophotometric quantification. The described decellularization regime produced full removal of native cells while maintaining the mechanical stability and the quantitative composition of the atrioventricular heart valve neoscaffolds. The surface of the xenogeneic matrix could be successfully reseeded with in vitro‐expanded human umbilical cord‐derived endothelial cells under physiological flow conditions. After complete decellularization with the detergent‐based protocol described here, physiological reseeding of the xenogeneic neoscaffolds resulted in the formation of a confluent layer of human umbilical cord‐derived endothelial cells. These results warrant further research toward the generation of atrioventricular heart valve neoscaffolds on the basis of decellularized xenogeneic tissue.